2016
DOI: 10.4236/ojop.2016.51005
|View full text |Cite
|
Sign up to set email alerts
|

Towards Optimizing a Personal Cooling Garment for Hot and Humid Deep Mining Conditions

Abstract: Workers exposed to hot and humid conditions suffer from heat stress that affects their concentration and can potentially lead to an increase in workplace accidents. To minimize heat stress, protective equipment may be worn, such as personal cooling garments. This paper presents and discusses the performances, advantages and disadvantages of existing personal cooling garments, namely air-cooled, liquid-cooled, phase change, hybrid, gas expansion and vacuum desiccant cooling garments, and a thermoelectric coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…These conditions can increase the risk of work accidents and even lead to death. Personal cooling garments can be worn [2] for minimizing heat stress, especially in places where effective air conditioning is not provided. A valid number of researchers have concluded that by controlling the cooling load of these garments, this would improve their efficiency and increase their autonomy [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…These conditions can increase the risk of work accidents and even lead to death. Personal cooling garments can be worn [2] for minimizing heat stress, especially in places where effective air conditioning is not provided. A valid number of researchers have concluded that by controlling the cooling load of these garments, this would improve their efficiency and increase their autonomy [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Currently existing cooling vests are not appropriate for use in deep mining conditions [17]. While the safety, efficiency and autonomy of the apparel will be more centric to the designers, comfort and ease of movement will be a top priority to convince miners to try out the cooling vest.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of cooling vests exist on the market [13][14][15][16], such as, air cooling garments, liquid cooling garments, cooling garments based on gas expansion, phase changing garments and thermoelectric cooling. In their work, Al Sayed et al [17] list the many issues that may arise when using an ordinary cooling vest in deep underground mines, such as reduced cooling efficiency, risk of condensation on the interior of the vest, bulkiness of the apparel and low autonomy [17]. They conclude that no cooling technology is perfectly compatible with deep mining environments.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the small cooling capacity and the reduced cooling effect of this approach can be sufficient for shallow mines, but it generally fails to meet the growing cooling requirements of deeper ones. The second category covers the artificial cooling technologies based on the advanced refrigeration principles, which solve the increasingly severe problem of thermal damage by using or combining centralized air conditioning, air pressurization, ice cooling, thermo-electric cooling with ethylene glycol, and high-temperature exchange machinery systems (HEMSs) [31][32][33][34][35][36][37]. The latter category of technologies have significantly reduced the high-temperature-induced thermal damage in some particular deep mines and resolved their cooling problems.…”
Section: Introductionmentioning
confidence: 99%